PELAKSANAAN PROGRAM GERAKAN LITERASI SEKOLAH PADA TAHAP PEMBIASAAN DI SDN 193 PEKANBARU - Lokita Anastasia Purnama Hsb; Zaka Hadikusuma Ramadan (JGK (Jurnal Guru Kita), 2022)
Abstract: Implementation of the School Literacy Movement Program at the Habituation Stage at Sdn 193 Pekanbaru. The background of this research is a government regulation that regulates the implementation schedule for the school literacy movement (GLS) in schools. The school literacy movement can help students understand information both verbally and in writing. The implementation of the habituation of the School Literacy Movement is one of the literacy activities and a form of government awareness of the importance of building a literacy culture in the world of education. This study aims to describe the implementation of the habituation of the School Literacy Movement at SDN 193 Pekanbaru. This type of research is a naturalistic inquiry. The subjects of this study were 1 principal and 2 homeroom teachers and 6 students. Research instruments in the form of interviews and observations. The data analysis technique in this study is the presentation of data and drawing conclusions. Based on the results of the study, it shows that the School Literacy Movement at the habituation stage has not been carried out properly due to the covid pandemic. This can be seen from the results of interviews, namely one of the teachers only carried out memca activities for 10 minutes, the activities of filling in the school and classroom magazines were not running, the reading interest of students who were still lacking, and lack of reading material.